Price to Book Value as a Moderator of Profitability Signals and Stock Prices: Evidence from Indonesia's Industrial Sector - Rifda Salsabila Putri Kholiq; M. Mustaqim (P3M Politeknik Negeri Banjarmasin, 2026)
To capture what genuinely steers stock values, this study dives into how ROA and ROE shape share prices in the industrial market, while tracking how Price-to-Book Value (PBV) moderates these connections. The scope centers on companies within the IDXINDUST Index on the Indonesia Stock Exchange over the 2022–2024 timeframe. Employing an explanatory quantitative method, the project draws on secondary data from a purposive sample of 42 firms, resulting in 126 panel data points. Data computation relied on panel regression models and MRA executed via EViews 13. Interestingly, the statistical output indicates that ROA plays no real role in shifting stock prices, whereas ROE shows a clear upward influence. PBV also emerged as a significant moderating force it tones down the impact of ROA but strongly reinforces the positive ties between ROE and stock values. These dynamics clearly demonstrate that modern investors do not evaluate profitability in a vacuum; instead, they integrate market valuation deeply into their investment choices.